2022
DOI: 10.1007/s12063-021-00231-x
|View full text |Cite
|
Sign up to set email alerts
|

Resilience strategies to recover from the cascading ripple effect in a copper supply chain through project management

Abstract: As the supply chains are growing and becoming more interdependent, the vulnerability and the chances of supply chain failure also increases. The supply chain industry is severely affected due to the COVID-19 outbreak and industry practitioners are focusing on minimizing the ripple effect of the disruption made to the economy. Considering the unprecedented situation, the research is motivated to analyse the ripple effect in a multi-echelon supply chain and investigate the performance at various nodes to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 69 publications
0
5
0
2
Order By: Relevance
“…This proposition, which connects the size of the company and its sector with its postpandemic performance, has been amply highlighted in the literature. Kek et al (2022) and Hemadoshini (2021) emphasised how different companies have shown variable levels of project performance post-pandemic and how this can significantly impact our understanding of future projects. Therefore, the interplay between a given sector and the size of a company operating in that sector has far-reaching consequences on project performance.…”
Section: Research Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…This proposition, which connects the size of the company and its sector with its postpandemic performance, has been amply highlighted in the literature. Kek et al (2022) and Hemadoshini (2021) emphasised how different companies have shown variable levels of project performance post-pandemic and how this can significantly impact our understanding of future projects. Therefore, the interplay between a given sector and the size of a company operating in that sector has far-reaching consequences on project performance.…”
Section: Research Frameworkmentioning
confidence: 99%
“…A significant drop in performance was observed during the execution stage of projects, which warrants looking at PM activities in detail. Kek et al (2022) investigated the ripple effect of the copper melting project across the globe from Tanzania to Saudi Arabia after the pandemic. They found lack of communication amongst stakeholders and an absence of resilience in all stages of the project to be the main disruptors to optimum performance.…”
Section: Manm 211mentioning
confidence: 99%
See 1 more Smart Citation
“…Van den Brink et al [36] represented the Cobalt SC by geographic mapping and globally positioning mines and refineries. K.E.K et al [37] represented a global copper supply chain model, establishing some copper-producing and copper-consuming countries. For mathematical modelling, Akbari-Kasgari et al [38] graphically represented the copper supply chain, from mine to final copper disposal.…”
Section: Explicate Problemmentioning
confidence: 99%
“…Disruptions, such as those caused by COVID-19, create ripple and bullwhip effects that create uncertainties in demand within and across whole industries (e.g. KEK et al 2022 ). In this context, flexibility is a main mean for firms to build resilience capability into their systems to survive and grow (Piprani et al 2022 ; Badhotiya et al 2022 ), specifically reconfigurability (Pansare and Yadav 2022 ).…”
Section: Introductionmentioning
confidence: 99%